Effects of mixing, sheeting, and cooking on the starch, protein, and water structures of durum wheat semolina and chickpea flour pasta. (30th October 2021) - Garcia-Valle, Daniel E.; Bello-Pérez, Luis A.; Agama-Acevedo, Edith; Alvarez-Ramirez, Jose
Highlights: The formation of protein network in chickpea flour pasta relied strongly on SH bonding. The processing stages increased the β-sheet structures in semolina pasta but not in chickpea pasta. Strongly bonded water structures are more abundant in chickpea flour pasta than in semolina pasta. Abstract: The influence of the pasta preparation stages on starch, proteins, and water structures of semolina and chickpea pasta was studied. The hydrated starch structures (995/1022 FTIR ratio) increased in semolina and reduced in chickpea pasta. The processing stages in semolina pasta led to a significant increase of β-sheet structures (~50% to ~68%). The β-sheet structures content in chickpea pasta was lower (~52%), and was most affected by sheeting and cooking. The water structure was assessed by the analysis of the OH fingerprint FTIR region (3700–2800 cm −1 ) and showing that water molecules (~90%) are strongly and moderately bound. The chickpea pasta displayed the highest content of strongly bonded water (about 55%) in contrast to the semolina pasta (~48%). A principal component analysis showed that the molecular organization of semolina pasta was mostly affected by dough formation and cooking; the molecular organization of chickpea pasta was determined by the cooking stage.